Controlling the Defects of Cs2AgBiBr6 by Varied Precursor Compositions. Issue 11 (7th July 2022) - Frebel, Alexander; Yoon, Songhak; Meles Neguse, Samuel; Jöckel, Dennis M.; Widenmeyer, Marc; Lange, Stefan; Naumann, Volker; Rosspeintner, Arnulf; Ebbinghaus, Stefan G.; Balke, Benjamin; Weidenkaff, Anke
Abstract : The amount and type of defects in Cs2 AgBiBr6 are controlled by varying the Ag/Bi ratio of the precursor solutions in two different synthesis routes, that is, slow solution cooling crystallization and fast microwave‐assisted hydrothermal synthesis. The correlation between the Ag/Bi ratio in the precursor solution and defect formation in the crystals is studied by band broadening analysis in Raman spectroscopy, the estimated Urbach energy in UV–vis spectroscopy, and thermogravimetric analysis. Ag‐rich precursors are found to prevent the formation of the secondary‐phase Cs3 Bi2 Br9, but at the same time induced the formation of Br vacancies and antisite defects. Time‐resolved photoluminescence measurements reveal that the formation of beneficial defects such as Br vacancies causes to trap the charge carriers, thus avoiding the recombination of charge carriers and leading to a longer carrier lifetime. Herein, the findings provide a guidance to decrease the defect densities and can be applied to the fabrication of Pb‐free solar cells based on Cs2 AgBiBr6 . Abstract : Schematic illustration of the induced dominant defects for Bi‐rich/stoichiometric conditions and Ag‐rich conditions. Light absorption, emission, and trapping/detrapping mechanisms of charge carriers are highlighted.